(untitled) (Revista de Ensino em Artes, Moda e Design, 2025)
Fashion is a form of cultural expression that is manifested through clothing, accessories, behaviors and style, all of which are relevant as a collective social phenomenon. In this sense, fashion encompasses not only dressing but also the arts in general, consumption patterns and linguistic expressions. As it follows trends, its lexicon is dynamic and wide. The naming process that shapes the lexical system is closely linked to human activity. In this phenomenon, the names of common fashion items that appear in magazines and are frequently present in wardrobes may reveal an onomastic origin. In this study, based on principles specifically related to Onomastics – the branch of Linguistics that investigates proper names, we aim to conduct a lexical-semantic analysis of certain items collected from the web over a twelve-year period, sourced from glossaries and exemplified by Vogue magazine. This analysis considers both their etymology and current meaning, through consultation of dictionaries and glossaries. The examination revealed, for instance, that the clothing item bermuda originates from a toponym; while strass, the brilliant stone used in accessories, derives from an anthroponym. We hope this research highlights the dynamic nature of language and how fashion serves as a fertile ground for rich lexical creations.